1992
DOI: 10.1038/ki.1992.148
|View full text |Cite
|
Sign up to set email alerts
|

Renal hypertrophy in streptozotocin diabetic rats: Role of proteolytic lysosomal enzymes

Abstract: Renal protein mass increases in diabetic renal hypertrophy. Accretion of protein may be the result of increased protein synthesis and/or decreased protein degradation. The lysosomal proteases, cathepsins B and L, are key enzymes in cellular protein catabolism. To evaluate the role of protein degradation in diabetic renal hypertrophy, the activities of cathepsins B and L were measured in microdissected proximal tubule segments and in kidney cortex homogenates. In rats four and ten days following induction of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
28
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 25 publications
4
28
0
1
Order By: Relevance
“…Our finding of a reduced fragmentation ratio of albumin in diabetes may correspond in part to decreased lysosomal activity and/or intracellular trafficking to and from the lysosome. This finding is consistent with findings in other studies that have shown that enzymes specifically associated with lysosomes have decreased activity in diabetes (22)(23)(24). However, it is possible that this change in enzyme activity only affects the size of the fragments excreted and not the quantity.…”
Section: Discussionsupporting
confidence: 83%
“…Our finding of a reduced fragmentation ratio of albumin in diabetes may correspond in part to decreased lysosomal activity and/or intracellular trafficking to and from the lysosome. This finding is consistent with findings in other studies that have shown that enzymes specifically associated with lysosomes have decreased activity in diabetes (22)(23)(24). However, it is possible that this change in enzyme activity only affects the size of the fragments excreted and not the quantity.…”
Section: Discussionsupporting
confidence: 83%
“…Renal lysosome activity. While lysosomal activity was decreased in diabetes, which is in agreement with other studies (41,42), it was not normalized by RAM. This finding is the most striking feature of the observations on lysosomal activi t y, for it means that a decrease in renal lysosomal activity is not required for the prevention of albuminuria.…”
Section: Discussionsupporting
confidence: 82%
“…This notion is consistent with earlier observations in diabetic animals where reduced renal proteolytic activity [7,8] and lower activities of lysosomal enzymes such as cathepsins L and B [9,10] and cathepsin D [11] have been reported. Reduced proteinase activity in turn may lead to hypertrophy and matrix accumulation, as it has been demonstrated that inhibition of lysosomal pro-teinases does suppress intracellular protein breakdown by up to 70 % [12].…”
supporting
confidence: 82%